The SCID Mouse Model for Identifying Virulence Determinants in Coxiella burnetii - van Schaik, Erin J. (Front Cell Infect Microbiol, 2017)
Coxiella burnetii is an intracellular, zoonotic pathogen that is the causative agent of Q fever. Infection most frequently occurs after inhalation of contaminated aerosols, which can lead to acute, self-limiting febrile illness or more serve chronic infections such as hepatitis or endocarditis. Macrophages are the principal target cells during infection where C. burnetii resides and replicates within a unique phagolysosome-like compartment, the Coxiella-containing vacuole (CCV). The first virulence determinant described as necessary for infection was full-length lipopolysaccarride (LPS); spontaneous rough mutants (phase II) arise after passage in immuno-incompetent hosts. Phase II C. burnetii are attenuated in immuno-competent animals, but are fully capable of infecting a variety of host cells in vitro. A clonal strain of the Nine Mile isolate (RSA439, clone 4), has a 26 KDa chromosomal deletion that includes LPS biosynthetic genes and is uniquely approved for use in BL2/ABL2 conditions. With the advances of axenic media and genetic tools for C. burnetii research, the characterization of novel virulence determinants is ongoing and almost exclusively performed using this attenuated clone. A major problem with predicting essential virulence loci with RSA439 is that, although some cell-autonomous phenotypes can be assessed in tissue culture, no animal model for assessing pathogenesis has been defined. Here we describe the use of SCID mice for predicting virulence factors of C. burnetii, in either independent or competitive infections. We propose that this model allows for the identification of mutations that are competent for intracellular replication in vitro, but attenuated for growth in vivo and predict essential innate immune responses modulated by the pathogen during infection as a central pathogenic strategy.